Animal constructions and technological knowledge - Shew, Ashley (Lexington Books, 2017)
Humans thinking about other animals – Technological knowledge – Ape and primate cases – Cetaceans – Birds – Spiderwebs, beaver dams, and other contrast cases – Human bias and technological knowledge
Literaturangaben
Keywords: Tool use in animals; Technology; Animal intelligence; Animal behavior